2021
DOI: 10.1186/s12887-021-02920-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of death or neurodevelopmental outcomes in extremely low birth weight preterm infants following different management options of haemodynamically significant patent ductus arteriosus

Abstract: Background Optimal management of haemodynamically significant patent ductus arteriosus (HsPDA) in premature babies remains controversial. Our aim is to compare death and/or adverse neurodevelopmental outcomes in extremely low birth weight (ELBW) infants with HsPDA who were managed with conservative [C], medical [M] and/or surgical [S] treatment, with secondary aim to examine short-term morbidities among [S] and [C] groups. The study also compared outcomes in very low birth weight (VLBW) infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…(14) Neurodevelopmental outcomes reported in premature infants with a hsPDA have been mixed. Some studies exhibited similar long-term outcomes in infants with a PDA regardless of the type of treatment (15) while other studies have shown worse NDI at 2-3 years of age in infants receiving either medical or surgical treatment. (16) Many investigators have correlated surgical ligation with negative neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 95%
“…(14) Neurodevelopmental outcomes reported in premature infants with a hsPDA have been mixed. Some studies exhibited similar long-term outcomes in infants with a PDA regardless of the type of treatment (15) while other studies have shown worse NDI at 2-3 years of age in infants receiving either medical or surgical treatment. (16) Many investigators have correlated surgical ligation with negative neurodevelopmental outcome.…”
Section: Introductionmentioning
confidence: 95%